Code mixing practices in Indonesian language learning by class VII teachers of Junior High School 45 of Surabaya - Sri Utami; Devito Andharu (Universitas Muhammadiyah Malang, 2025)
This qualitative descriptive study examines code mixing practices in Indonesian language learning among seventh-grade teachers and students at State Junior High School 45 of Surabaya. It focuses on identifying the types, forms, causes, functions, and impacts of code mixing in classroom activities. Data were gathered through observation and teacher questionnaires. Findings show various forms of code mixing, including word, phrase, clause, baster, and repeated word insertions. Both inward and outward code mixing types were observed. Factors contributing to code mixing include urgency, second-party influence, emphasis, habitual relaxed communication, and speaker duality. Functionally, code mixing helps clarify meaning, fosters familiarity, maintains communication, and strengthens local cultural identity. It is used to create a more relaxed and engaging learning environment, encouraging student participation and improving comprehension. However, it also poses a risk to students’ proficiency in standard Indonesian, as they may become too reliant on regional language. Despite this drawback, the overall impact of code mixing in this context is largely positive, enhancing student understanding and classroom interaction.